The Role of Macrophytes in Biogenic Silica Storage in Ivory Coast Lagoons - Koné, Yefanlan Jose-Mathieu; Van de Vijver, Bart; Schoelynck, Jonas (Frontiers in Earth Science, 2019)
Lagoons are shallow aquatic environments that typically show a broad variety in colonization by macrophytes. We present the biogenic silica (BSi) data obtained from eleven macrophyte species randomly collected in three small lagoons (Ono, Kodjoboue and Hebe) of Ivory Coast during twelve consecutive months. BSi concentrations were different between species and between lagoons with average values ranging from 2 to 36 mg g-1. The highest values were found in Hebe and Kodjoboue lagoons due to the dominance of emergent plant species belonging to Poaceae and Cyperaceae families. However, because total plant coverage was low (5 % of the lagoon surface), the total BSi stock in vegetation was low (0.2 and 6.1 t, respectively). Oppositely, lower BSi concentrations were found in plants from Ono lagoon, yet the abundance of macrophytes covered 66% of its surface area which resulted in a larger vegetation BSi stock (17.4 t). Dissolved silica in surface water varied seasonally between 1.7 and 10.8 mg L-1, and is assumed to be linked to diatom blooms rather than to macrophyte uptake. Sediment data showed that the three lagoons store a large quantity of BSi in their sediments with values ranging from 2 to 8 t BSi ha-1. Because of macrophyte influence in these lagoons, macrophyte phytoliths were expected to contribute significantly to this sediment BSi stock. However, microscopic analysis revealed that this stock is absolutely dominated by diatom frustules and sponge spicules rather than plant phytoliths. We conclude that macrophytes in these lagoons contribute only marginally to BSi storage in sediments but that fragile phytogenic silica structures may affect local silica cycling.